Taxonomic review and evolutionary trends of Levipustulini and Absenticostini (Brachiopoda) from Argentina: palaeobiogeographic and palaeoclimatic implications - Taboada, Arturo Cesar (2011)
The diagnosis and composition of the brachiopod Tribe Levipustulini Lazarev, 1985 is reviewed, leading to a detailed revision of the genera Levipustula Maxwell, 1951 and Lanipustula Klets, 1983, as well as a review of previous records of the species Levipustula levis Maxwell from Australia and Argentina. The presence of Lanipustula patagoniensis Simanauskas in Patagonia is confirmed with additional topotypic material described and illustrated. Based on this review, we reassign Levipustula levis from New South Wales, Australia to Lanipustula. Two new species, Lanipustula kletsi from the middle Pennsylvanian of Patagonia and the Absenticostinin Absenticosta bruntoneileenae from the latest Viséan of western Argentina, are proposed. Abstenticosta bruntoneileenae is suggested as a possible ancestral stock of the Patagonian Levipustulini through the lineage  Lanipustula-Verchojania-Jakutoproductus-Piatnitzkya (Serpukhovian-middle Artinskian). The development of similar phylogenetic lineages of Levipustulini in high latitude regions of both northern and southern hemispheres (such as Siberia in Northeast Asia and Patagonia in southwestern Gondwana) is here interpreted as a consequence of parallel evolution.  The progressive palaeobiogeographic isolation of Patagonia from mainland South America, coupled with its southward drift under cold palaeoclimatic conditions during middle Carboniferous-earliest Permian times, is proposed to have triggered the Levipustulini vicariance.